THE USE OF ICT IN THE MANAGEMENT OF SCHOOLS OF GENERAL EDUCATION IN THE FORMING OF CIVIL SOCIETY - Sergiy I. Netyosov (Інформаційні технології і засоби навчання, 2013)
The status and character of the use of ICT in the management of schools of general education and related utilization of information technology in the organization of management of educational institutions with the requirements of the formation of civil society is considered in the article. The author proves that the management of general education institutions involves a significant amount of social information, and the use of ICT in these activities contributes to the inclusion of the public in the mission of education. But the actual state of realization of ICTs in management of secondary schools is mainly directed at the use of technocratic information technology capabilities and the realization of social component in the management of institutions of general education is involved partially, that is an indicator of the rather slow progress of Ukraine toward the establishment of a civil society.